Waqf empowerment for the autonomy of Islamic boarding school (pesantren); study of modern Islamic boarding school (pondok) Tazakka Batang - Subhi Mahmassani (Journal of Islamic Economics, Management, and Business (JIEMB), 2020)
Purpose – This study aims to study waqf instrument developed by modern Islamic boarding school (pondok) Tazakka, Batang.Method – This study is a qualitative field research, which utilizes observation, interview, and documentation. The character of this research is descriptive analysis.Result – Modern pondok of Tazakka uses at least six different waqf program as a financial source of their activities. These programmes are asset waqf, cash waqf, productive waqf, benefits waqf, profession waqf, and transfer of rights waqf. The programmes help the pondok to be more autonomous and able to provide various benefits for the scholars of the pondok and the people surround it. Implication – This research gives illustration of waqf management in an Islamic boarding school. By understanding the mechanism of the waqf management, hopefully Islamic boarding schools in Indonesia able to empower themselves better.Originality – A lot of Islamic boarding schools use waqf for his research is among the few researchs which taking a perspective of empowering religious social organization in Indonesia.